C1QBP regulates mitochondrial plasticity to impact tumor progression and antitumor immune response - Wang, Qiping; Chai, Dafei; Sobhani, Navid; Sun, Nan; Neeli, Praveen; Zheng, Junnian; Tian, Hui (Frontiers in Physiology, 2022)
Mitochondrial plasticity including mitochondrial dynamics, metabolic flexibility, and mitochondrial quality control, impact tumor cells' progression and determine immune cells' fate. Complement C1q binding protein (C1QBP) plays an indispensable role through regulating mitochondrial morphology, metabolism, and autophagy. C1QBP promotes mitochondrial plasticity to impact tumor metastasis and their therapeutic response. At the same time, C1QBP is involved in regulating immune cells’ maturation, differentiation, and effector function through the enhancement of mitochondrial function. In this regard, manipulation of C1QBP has been shown to adjust the competitive balance between tumor cells and immune cells. In the course of evolution, mitochondrial plasticity has endowed numerous advantages against the relentless microenvironment of tumors. In this current review, we summarize the current knowledge of the mechanism of C1QBP regulation of cancer and immunity. We explain this process in vision of potentially new anticancer therapies.